1963 Enrico Fermi Award Presentation - Lawrence Berkeley National Laboratory. Technical and Electronic Information Department (1963)
Black and white photograph depicting the presentation ceremony of the Erico Fermi Award to J. Robert Oppenheimer (1904-1967) at the White House. Pictured left to right are Glenn Seaborg (1912-1999), Lyndon B. Johnson (1908-1973), Martha Parsons (n.d.), Dr. Oppenheimer, Peter Oppenheimer (1941-), Katherine "Kitty" Oppenheimer (1910-1972), Claudia "Lady Bird" Johnson (1912-2007), Robert Wilson (1914-2000), Helen L. Seaborg (1917-2006), and James T. Ramey (1915-2010). The Enrico Fermi Presidential Award is one of the oldest and most prestigious science and technology honors bestowed by the U.S. Government. The Fermi Award is annually conferred by the President of the United States to honor scientists, engineers, or science policymakers who have achieved excellence in research in energy science and technology benefiting mankind.
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; Johnson, Lyndon B. (Lyndon Baines), 1908-1973; Oppenheimer, J. Robert, 1904-1967; Science--Awards; Nobel Prize winners